2006
DOI: 10.1037/1528-3542.6.3.356
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous emotion regulation during evaluated speaking tasks: Associations with negative affect, anxiety expression, memory, and physiological responding.

Abstract: In these studies, the correlates of spontaneously using expressive suppression and cognitive reappraisal during stressful speeches were examined. Spontaneous emotion regulation means that there were no instructions of how to regulate emotions during the speech. Instead, participants indicated after the speech to what extent they used self-motivated expressive suppression or reappraisal during the task. The results show that suppression is associated with less anxiety expression, greater physiological respondin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
195
5
5

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 223 publications
(216 citation statements)
references
References 52 publications
11
195
5
5
Order By: Relevance
“…Thus, trauma-exposed individuals who used expressive suppression were no more or less likely to use cognitive reappraisal or vice versa. Further, this lack of strong association is also consistent with a recent study using a stress-inducing evaluative speech paradigm (Egloff et al, 2006). Given that repeated and prolonged exposure to interpersonal trauma may lead to emotion regulation difficulties beyond or in the absence of diagnosable PTSD (e.g., Frewen & Lanius, 2006;Pelcovitz et al, 1997;van der Kolk et al, 2005), our finding of independence of these emotional regulation strategies needs to be further replicated with samples such as those experiencing childhood sexual abuse.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Thus, trauma-exposed individuals who used expressive suppression were no more or less likely to use cognitive reappraisal or vice versa. Further, this lack of strong association is also consistent with a recent study using a stress-inducing evaluative speech paradigm (Egloff et al, 2006). Given that repeated and prolonged exposure to interpersonal trauma may lead to emotion regulation difficulties beyond or in the absence of diagnosable PTSD (e.g., Frewen & Lanius, 2006;Pelcovitz et al, 1997;van der Kolk et al, 2005), our finding of independence of these emotional regulation strategies needs to be further replicated with samples such as those experiencing childhood sexual abuse.…”
Section: Discussionsupporting
confidence: 89%
“…Nonclinical studies manipulating expressive suppression (Richards & Gross, 2000; for a review, see Gross, 2002), examining individual differences (e.g., Gross & John, 2003;, and using more hybrid designs (Egloff et al, 2006) are surprisingly consistent with the current study; expressive suppression is emerging as a reliably costly strategy associated with negative psychological outcomes. In particular, inhibited emotional expression may be a maladaptive strategy when applied inflexibly (e.g., .…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In contrast, studies of reappraisal have demonstrated successful reduction of emotion expression along with decreased negative affect, non-significant reductions in physiological response (Egloff et al, 2006;Gross, 1998a;Gross & John, 2003;Richards & Gross, 2000), and reduced amygdala activation (Goldin et al, 2008;Ochsner et al, 2004).…”
mentioning
confidence: 99%
“…Such studies have demonstrated that suppression is associated with reduced retrieval (Bonanno, Papa, Lalande, Westphal, & Coifman, 2004;Egloff et al, 2006;Richards & Gross, 1999, 2000, while reappraisal is associated with unaltered (Egloff et al, 2006;Richards & Gross, 2000) or with enhanced retrieval (Dillon, Ritchey, Johnson, & LaBar, 2007;Richards & Gross, 2000). However, these studies all used very short-term retention tests (10 min; Dillon et al, used 1 h).…”
mentioning
confidence: 99%